Familial correlates of adolescent girls' physical activity, television use, dietary intake, weight, and body composition - Hannan Peter J; Fulkerson Jayne A; Neumark-Sztainer Dianne; Bauer Katherine W; Story Mary (BMC, 2011)
Abstract Background The family environment offers several opportunities through which to improve adolescents' weight and weight-related behaviors. This study aims to examine the cross-sectional relationships between multiple factors in the family environment and physical activity (PA), television use (TV), soft drink intake, fruit and vegetable (FV) intake, body mass index (BMI), and body composition among a sample of sociodemographically-diverse adolescent girls. Methods Subjects included girls (mean age = 15.7), 71% of whom identified as a racial/ethnic minority, and one of their parents (dyad n = 253). Parents completed surveys assessing factors in the family environment including familial support for adolescents' PA, healthful dietary intake, and limiting TV use; parental modeling of behavior; and resources in the home such as availability of healthful food. Girls' PA and TV use were measured by 3-Day Physical Activity Recall (3DPAR) and dietary intake by survey measures. BMI was measured by study staff, and body fat by dual-energy X-ray absorptiometry (DXA). Hierarchical linear regression models tested individual and mutually-adjusted relationships between family environment factors and girls' outcomes. Results In the individual models, positive associations were observed between family support for PA and girls' total PA (p = .011) and moderate-to-vigorous PA (p=.016), home food availability and girls' soft drink (p < .001) and FV (p < .001) intake, and family meal frequency and girls' FV intake (p = .023). Across the individual and mutually-adjusted models, parental modeling of PA, TV, and soft drink and FV intake was consistently associated with girls' behavior. Conclusions Helping parents improve their physical activity and dietary intake, as well as reduce time watching television, may be an effective way to promote healthful behaviors and weight among adolescent girls.